English Skills and Early Labour Market Integration: Evidence from Humanitarian Migrants in Australia - Zhiming Cheng; Ben Zhe Wang; Zhou Jiang; Lucy Taksa; Massimiliano Tani (Global Labor Organization (GLO), 2020)
We use the panel data from the Building a New Life in Australia survey to examine the relationships between proficiency in English and labour market outcomes among humanitarian migrants. Having better general or speaking skills in English is certainly associated with a higher propensity for participation in the labour force and getting a job. However, we also find that, compared to other domains of English proficiency, such as listening, reading and writing, proficiency in English speaking skills has been the least improved domain for humanitarian migrants' who have participated in an English training program. Our paper explores the channels leading to these outcomes, finding that self-esteem, self-efficacy and general health partially mediate the relationship between English proficiency and labour force participation. We also find that self-efficacy, general health and indicative serious mental illness partially mediate the relationship between better English proficiency and the chance of getting a job.
Keywords: 330; Australia; humanitarian migrant; proficiency in English; labour force participation; employment